Implementation of a revised classification for intrapartum fetal heart rate monitoring and association to birth outcome: A national cohort study - Maria Jonsson; Jonas Söderling; Lars Ladfors; Lennart Nordström; Marianne Nilsson; Michael Algovik; Mikael Norman; Malin Holzmann (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction A revised intrapartum cardiotocography (CTG) classification was introduced in Sweden in 2017. The aims of the revision were to adapt to the international guideline published in 2015 and to adjust the classification of CTG patterns to current evidence regarding intrapartum fetal physiology. This study aimed to investigate adverse neonatal outcomes before and after implementation of the revised CTG classification. Material and Methods A before‐and‐after design was used. Cohort I (n = 160 210) included births from June 1, 2014 through May 31, 2016 using the former CTG classification, and cohort II (n = 166 558) included births from June 1, 2018 through May 31, 2020 with the revised classification. Data were collected from the Swedish Pregnancy and Neonatal Registers. The primary outcome was moderate to severe neonatal hypoxic ischemic encephalopathy (HIE 2–3). Secondary outcomes were birth acidemia (umbilical artery pH <7.05 and base excess < −12 mmol/L or pH <7.00), A‐criteria for neonatal hypothermia treatment, 5‐min Apgar scores <4 and <7, neonatal seizures, meconium aspiration, neonatal mortality and delivery mode. Logistic regression was used (period II vs period I), and results are presented as adjusted odds ratios (aORs) with 95% confidence intervals (95% CIs). Results There were no statistically significant differences in HIE 2–3 (aOR 1.27; 95% CI 0.97–1.66), proportion of neonates meeting A‐criteria for hypothermia treatment (aOR 0.96; 95% CI 0.89–1.04) or neonatal mortality (aOR 0.68; 95% CI 0.39–1.18) between the cohorts. Birth acidemia (aOR 1.36; 95% CI 1.25–1.48), 5‐min Apgar scores <7 (aOR 1.27; 95% CI 1.18–1.36) and <4 (aOR 1.40; 95% CI 1.17–1.66) occurred more often in cohort II. The absolute risk difference for HIE 2–3 was 0.02% (95% CI 0.00–0.04). Operative delivery (vacuum or cesarean) rates were lower in cohort II (aOR 0.82; 95% CI 0.80–0.85 and aOR 0.94; 95% CI 0.91–0.97, respectively). Conclusions Although not statistically significant, a small increase in the incidence of HIE 2–3 after implementation of the revised CTG classification cannot be excluded. Operative deliveries were fewer but incidences of acidemia and low Apgar scores were higher in the latter cohort. This warrants further in‐depth analyses before a full re‐evaluation of the revised classification can be made.